PEMANTAUAN SEDIMENTASI TOTAL SUSPENDED SOLID (TSS) DI WADUK KEDUNGOMBO PERIODE 2014-2018 BERBASIS CITRA LANDSAT 8 - Abdi Sukmono; Trevi Austin Rajagukguk; Sawitri Subiyanto; Nurhadi Bashit (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2018)
Sedimentation is a problem that often occurs in reservoirs in Indonesia. One reservoir that has the potential to be affected by sedimentation is the Kedungombo Reservoir. The water volume of the Kedungombo dam is estimated to shrink 40% of the planned water volume due to the sedimentation problem. The condition of the reservoir water needs to be monitored periodically to determine the development of sedimentation in the reservoir area. The large reservoir area of 6,000 ha requires considerable energy and cost if monitoring is done conventionally. Remote sensing technology with Landsat-8 satellite imagery can be used as an alternative technology that is more efficient in reservoir sedimentation monitoring. Reservoir sedimentation monitoring can be observed from the development of the value of total suspended solid (TSS).. The results of multitemporal TSS processing for the period 2014-2018 showed that the quality of the Kedongombo Reservoir TSS generally began to improve despite high sedimentation in some areas. The class of heavily polluted / sedimentated TSS decreased from 380, 97 Ha in 2014 to 353.61 Ha in 2014 and continued to improve to an area of 120.96 Ha in 2018. But at the estuary of Laban Sub-watershed and Ivory Sub-watershed TSS remained has a high concentration.